2014
DOI: 10.1186/1744-8069-10-15
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Peripheral KCNQ Channels Attenuates Inflammatory Pain

Abstract: BackgroundRefractory chronic pain dramatically reduces the quality of life of patients. Existing drugs cannot fully achieve effective chronic pain control because of their lower efficacy and/or accompanying side effects. Voltage-gated potassium channels (KCNQ) openers have demonstrated their analgesic effect in preclinical and clinical studies, and are thus considered to be a potential therapeutic target as analgesics. However, these drugs exhibit a narrow therapeutic window due to their imposed central nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 57 publications
2
48
0
Order By: Relevance
“…Importantly, XE991 reverted H 2 S donors effects at dosages that did not modify oxaliplatinhypersensitivity per se (present data). Furthermore, XE991 did not show anti-nociceptive properties since it did not modify the normal pain threshold of naïve animals (Blackburn-Munro and Jensen, 2003;Hayashi et al, 2014). These data led us to hypothesize that H 2 S, by activating Kv7 channels, reduces neuronal hyperexcitability both in DRG and in central neurons, thus normalizing the altered electrophysiological activity occurring during chemotherapyinduced neuropathic pain (Di Cesare Mannelli et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, XE991 reverted H 2 S donors effects at dosages that did not modify oxaliplatinhypersensitivity per se (present data). Furthermore, XE991 did not show anti-nociceptive properties since it did not modify the normal pain threshold of naïve animals (Blackburn-Munro and Jensen, 2003;Hayashi et al, 2014). These data led us to hypothesize that H 2 S, by activating Kv7 channels, reduces neuronal hyperexcitability both in DRG and in central neurons, thus normalizing the altered electrophysiological activity occurring during chemotherapyinduced neuropathic pain (Di Cesare Mannelli et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…The Kv7 channel opening activity may produce an analgesic effect by blocking action potentials throughout the CNS and peripheral nerves. Recent studies have shown that peripheral sensory neurons may be the main target through which retigabine induces analgesia [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Coassembled KCNQ2 and KCNQ3 subunits were originally identified as components of the classic M channel [4]. KCNQ2/Q3 channels are expressed at a number of key locations in the pain transmission pathway, including the cerebral cortex, the spinal cord and the nociceptive dorsal root ganglia (DRG) neurons [5]. Functional studies have shown that firing in these neurons can be inhibited by a KCNQ2/Q3 activator.…”
Section: Introductionmentioning
confidence: 99%